Defect formation in CsI-CsBr mixed crystals - Garapyn, I.V.; Hud, I.Z.; Pavlyk, B.V. (Functional Materials, 2005)
The defect structure of Csl-CsBr mixed crystals has been studied by electroconductivity and thermostimulated depolarization current (TSDC) methods. The formation of Csl₀.₉₃Br₀.₀₇ solid solution is found to be accompanied by increase of conductivity as compared to that of pure Csl. The physical processes causing the appearаnce of TSDC maxima at 300 К and 385 К have been considered. The results obtained evidence the increase of anion vacancy concentration and unchanged concentration of cation vacancies in Csl₀.₉₃Br₀.₀₇ mixed crystals.